2018
DOI: 10.1302/0301-620x.100b4.bjj-2017-0891.r1
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of patient experience of an open fracture of the lower limb during acute care

Abstract: Recovery activities require an increased focus on emotional wellbeing. Surgeons are aware of the need for clinical expertise and for adequate pain relief but may not be as aware that their patients require support regarding their body image and help to imagine their future life. Cite this article: Bone Joint J 2018;100-B:522-6.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 13 publications
1
53
0
Order By: Relevance
“…We have specifically focussed on the longer term (2–4-years postinjury) impact of these injuries and especially in those patients who were identified as having injuries on the ‘severe’ end of the spectrum. We found that the concept of embodied vulnerability,3 9 and endurance in early recovery,8 clearly identified in acute care, also extends into the longer term as participants struggle to recover, processing their loss, working to negotiate how they live and integrate changes within their self-identity. Our findings indicate that longer term clinical support is required to improve outcomes for mental health, function, management of pain and living with disability in patients with major trauma to the lower limbs.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…We have specifically focussed on the longer term (2–4-years postinjury) impact of these injuries and especially in those patients who were identified as having injuries on the ‘severe’ end of the spectrum. We found that the concept of embodied vulnerability,3 9 and endurance in early recovery,8 clearly identified in acute care, also extends into the longer term as participants struggle to recover, processing their loss, working to negotiate how they live and integrate changes within their self-identity. Our findings indicate that longer term clinical support is required to improve outcomes for mental health, function, management of pain and living with disability in patients with major trauma to the lower limbs.…”
Section: Discussionmentioning
confidence: 88%
“…This qualitative study adds to recent research on the patient experience of open fractures of the lower limb in acute care3 9 and postinjury4 by identifying the ongoing recovery undertaken by patients to process the impact of injury on their sense of being disempowered, being changed and being myself. We have specifically focussed on the longer term (2–4-years postinjury) impact of these injuries and especially in those patients who were identified as having injuries on the ‘severe’ end of the spectrum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Open lower limb fractures can be life-changing injuries. Even when complication rates are low, a recent randomised multi-centre study has shown signi cant levels of patient reported disability throughout the rst 12 months post-injury (3,25,26). In this study of 427 patients who completed the trial, DRI scores improved from the mid-sixties at 3 months to mid-forties at 12 months.…”
Section: Discussionmentioning
confidence: 65%
“…The first was to examine patient experience of traumatic injury, in this case open-fracture of the lower limb. This experience is reported separately [ 5 , 6 ]. The second is reported here and describes the patient experience of being part of a trial in the context of emergency interventions.…”
Section: Introductionmentioning
confidence: 99%